Environmental Panels as a Proxy for Nursing Facility Patients With Methicillin-Resistant Staphylococcus aureus and Vancomycin-Resistant Enterococcus Colonization. (2nd May 2018) - Cassone, Marco; Mantey, Julia; Perri, Mary Beth; Gibson, Kristen; Lansing, Bonnie; McNamara, Sara; Patel, Payal K; Cheng, Vincent C C; Walters, Maroya S; Stone, Nimalie D; Zervos, Marcus J; Mody, Lona
Abstract: Background: Most nursing facilities (NFs) lack methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococcus (VRE) surveillance programs due to limited resources and high costs. We investigated the utility of environmental screening of high-touch surfaces in patient rooms as a way to circumvent these challenges. Methods: We compared MRSA and VRE culture data from high-touch surfaces in patients' rooms (14450 samples from 6 NFs) and ranked each site's performance in predicting patient colonization (7413 samples). The best-performing sites were included in a MRSA- and a VRE-specific panel that functioned as a proxy for patient colonization. Molecular typing was performed to confirm available concordant patient-environment pairs. Results: We identified and validated a MRSA panel that consisted of the bed controls, nurse call button, bed rail, and TV remote control. The VRE panel included the toilet seat, bed controls, bed rail, TV remote control, and top of the side table. Panel colonization data tracked patient colonization. Negative predictive values were 89%–92% for MRSA and 82%–84% for VRE. Molecular typing confirmed a strong clonal type relationship in available concordant patient-environment pairs (98% for MRSA, 91% for VRE), pointing to common epidemiological patterns for environmental and patient isolates. Conclusions: Environmental panels used as a proxy for patient colonization and incorporated into facility surveillance protocols can guide decolonization strategies, improve awareness of MRSA and VRE burden, and inform efforts to reduce transmission. Targeted environmental screening may be a viable surveillance strategy for MRSA and VRE detection in NFs. Abstract : Surveillance for antimicrobial-resistant organisms in nursing facilities is critically important but challenging. We developed simple panels of environmental sites that can be used as a proxy for determining nursing facility patient methicillin-resistant Staphylococcus aureus and vancomycin-resistant Enterococcus colonization.